GAMBARAN PENGETAHUAN, SIKAP, MOTIVASI, DAN SUPERVISI PADA PERAWAT DALAM PELAKSANAAN KESELAMATAN PASIEN (PATIENT SAFETY) DI INSTALASI RAWAT INAP RSUD SANJIWANI GIANYAR - Krissita, Ni Putu Amanda Ayuning; Suarjana, I Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022, 2022)
ABSTRACT Patient safety is basis of health services and an obligation that must be provided. This study aims describe the knowledge, attitudes, motivation, and supervision of nurses in implementation of patient safety. This study is descriptive observational study with a cross-sectional design. Informants in this study consisted of 127 nurses using total sampling technique. The data collection instrument used a questionnaire. Data analysis was carried out univariate and bivariate. The results of this study shows picture of good knowledge (63.78%) positive attitude (51.97%), good motivation (53.54%) good supervision (66.14%) and good patient safety implementation (3.54%). Knowledge, motivation, and supervision have a significant relationship in the implementation of patient safety, however, the attitude variable doesn’t have a significant relationship. Therefore, it’s necessary to do based on the results of this study is to conduct training on patient safety incident reporting guidelines to nurses and provide reward system to nurses according to their performance in implementing patient safety. Keywords: Patient Safety, Motivation, Knowledge, Attitude, and Supervision.